Telegram from Kelly L. Elmore to Max Bredig, May 20, 1946 - Elmore, Kelly L. (1946)
Kelly L. Elmore of the Tennessee Valley Authority sends a telegram to Max Albert Bredig (1902-1977) about his new job in Tennessee.
Keywords: Tennessee Valley Authority; Bredig, Max Albert, 1902-1977; Housing